Immunogenicity and safety of monovalent influenza A (H1N1) 2009 in HIV-infected Thai children - Phongsamart W. (2014)
To evaluate the immunogenicity and safety of the monovalent pandemic influenza A (H1N1) 2009 (pH1N1) vaccine in HIV-infected Thai children, 2 doses, 28days apart, of non-adjuvant monovalent pH1N1 vaccine (Panenza® by Sanofi Pasteur, 15μg/dose) provided by the National Health Promotion Program of the Thai Ministry of Public Health were given to HIV-infected children. Immunogenicity was measured by hemagglutination inhibition test (HAI) using two antigens, pH1N1 (A/Thailand/104/09) and seasonal influenza A H1N1 (A/Brisbane/59/07-like), at baseline, and 28days after each dose. Serologic response was defined as four-fold rising of HAI titer or HAI titer ≥1:40 for those with baseline titer ≤1:10. Adverse events were recorded for 7days after each vaccination. Of the 119 HIV-infected children enrolled, 60 (50.4%) were female with a median (IQR) age of 10.4 (7.2-13.7)years. All but 2 (98.3%) children were receiving antiretroviral therapy. At baseline, the median CD4 cell count was 782 (570-1149)cells/mm3, 91 (80.5%) children had HIV RNA level <40copies/ml. The baseline HAI titer ≥1:40 for pH1N1 and seasonal H1N1 were 45.4%, and 39.5%, respectively. At 28days after doses 1 and 2, the serologic response rates for pH1N1 were 54.2% and 67.8% with the geometric mean titer of 109.9 and 141.8; and serologic response rate when tested with seasonal H1N1 were 2.5% and 3.5%, respectively. The presence of baseline HAI titer for pH1N1 or seasonal H1N1 was found to be associated with serologic response. The vaccine was well tolerated. The results suggested that monovalent pH1N1 vaccine was immunogenic and safe in well controlled HIV-infected children with low level of cross reacting antibody to seasonal H1N1. © 2011 Elsevier Ltd.